Supplementation Effect of Herbal and Organic Minerals in Beef Cattle Feed on Consumption, Digestibility, Efficiency and Daily Gain - Prayitno, CH; Sutardi, TR; Suwarno, Suwarno (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. The experiment was conducted in an attempt to study the effect of supplementation of Sapindus rarak, garlic powder and its combinations in beef cattle feed enriched with organic minerals of Cr and Zn on feed consumption, feed digestibility, feed efficiency, daily gain of beef cattle. The study used 16 males Brahman cross cows, which were fed with feeds supplemented with 250 ppm Sapindus rarak powder, 250 ppm Garlic powder, and a combination of 250 ppm garlic-Sapindus rarak enriched with Cr and Zn mineral. The results showed that supplementation of Sapindus rarak, garlic and enriched organic minerals increased the consumption of dry matter, organic matter, digestibility of dry and organic matter, daily gain, feed efficiency, and reduced the population of rumen protozoa and bacteria. Conclusively, supplementation with 250 ppm garlic powder and Cr-Zn organic minerals was the best for beef cattle feed to improve daily gain and feed efficiency. Key words : Sapindus rarak, garlic, Cr-Zn, beef cattle, feed efficiency Abstrak. Penelitian dilaksanakan bertujuan untuk mengkaji pengaruh suplementasi tepung Sapindus rarak, garlic maupun kombinasinya yang diperkaya dengan mineral organik Cr dan Zn terhadap konsumsi pakan, kecernaan pakan, pertambahan bobot badan dan efisiensi pakan sapi potong. Penelitian menggunakan 16 ekor sapi Brahman cross, yang diberikan 250 ppm tepung Sapindus rarak, 250 ppm tepung Garlic dan 250 ppm tepung Sapindus rarak dan garlic yang diperkaya dengan mineral Cr dan Zn. Hasil penelitian menunjukkan, bahwa suplementasi tepung Sapindus rarak maupun garlic yang diperkaya mineral organik meningkatkan konsumsi bahan kering, bahan organik, kecernaan bahan kering dan bahan organik, pertambahan bobot badan, efisiensi pakan dan menurunkan populasi protozoa dan bakteri rumen. Suplementasi 250 ppm tepung garlic dan mineral organik Cr-Zn merupakan suplemen terbaik pada pakan sapi potong untuk meningkatkan bobot badan dan efisiensi pakan. Kata kunci : Sapindus rarak, bawang, Cr-Zn, sapi potong, efisiensi pakan